Poisoning by herbal medicines - Simões , Deise Vimaana Santos de Souza; Freitas , João Fábio de; Marques , Gyovana Oliveira (Seven Editora, 2024)
This article addresses the topic of herbal poisoning, highlighting the risks associated with the inappropriate use of medicinal plants and herbs, the methods of prevention, and the regulation of these products. The variety of herbal medicines, the possibility of contamination, incorrect dosages, drug interactions, side effects, toxicity and risk groups are explored. Also emphasized is the importance of consulting with healthcare professionals before using herbal medicines and being aware of the potential risks. DOI:https://doi.org/10.56238/sevened2024.007-049